Analysis of Factors Influencing Children's Nutritional Status in Kuta Onan Public Elementary School, Sub-District Sttu Jehe District Pakpak Bharat - Nurmaya Christina Sihite; Zuraidah Zuraidah; Asriwati Asriwati (The International Science of Health Journal, 2024)
Child nutrition remains a significant issue worldwide. According to World Health Organization (WHO) data from 2022, the global prevalence of underweight children is around 26.3%, with 95.2 million children affected. In the local context, Puskesmas data reveals that 43% of children are still malnourished. This study aims to analyze the factors influencing the nutritional status of children at Kuta Onan Public Elementary School, STTU Jehe District, Pakpak Bharat Regency. The research employs an Analytical Survey method with a Cross-Sectional approach. The population consists of 267 students, with a sample of 73 students selected through Proportional Sampling. Data analysis includes univariate, bivariate with chi-square tests, and multivariate with logistic regression. The findings indicate significant influences from knowledge (p = 0.000), feeding patterns (p = 0.003), parenting (p = 0.001), and a history of infectious diseases (p = 0.001) on nutritional status. Notably, knowledge emerged as the most dominant factor, with a risk 41 times greater than other variables. Income and physical activity showed no significant effect. The study concludes that enhancing parents' knowledge about nutritious food intake and providing a balanced diet are crucial steps in improving children's nutritional status in this region.